A performance comparison between NoSQL databases: MongoDB and ArangoDB - Treviño-Villalobos, Marlen (2019)
Currently, a large amount of information and data is generated, which is why alternative solutions appear to what already exists, such as non-relational databases or NoSQL, these databases work better with a large volume of data compared to the SQL. However, several investigations have been published regarding the performance of NoSQL databases, but there is not much information about the behavior of these Database Management Systems (DBMS) with geographic data, that is why this article raises a comparison in terms of the response time between the MongoDB and ArangoDB DBMS. To make this comparison, tests were carried out in two test scenarios, called 100% reading and 95% reading–5% writing. In addition, 10 different operation sizes were executed for both scenarios. The results obtained allow to conclude that, in both scenarios studied, the SGBD that presented a better performance was that of MongoDB.